Video viewing and streaming enhancement - Khalifa, Othman Omran; Yazeer, Mohamed Jameel Yazeer (2014)
The explosive growth of computing and multimedia information communications has led to human machine interaction in daily life. The increasing demand for multimedia information on the web, streaming video over the Internet has received tremendous attention from academia and industry. Transmission of real-time video typically has bandwidth, delay and loss requirements. However, the current effort does not guarantee the quality of service (QoS) to video viewing and streaming. Even though there is many video viewing and streaming applications, but still lagging of enhancements techniques. Furthermore, for video multicast, it is difficult to achieve both efficiency and flexibility. Thus, video viewing and streaming poses many challenges. To address these challenges, extensive research has been conducted. . In this paper, we are concerned with video viewing and streaming Enhancement, which refers to real- time transmission of stored video. A mechanism should exist to estimate the network conditions so as to adapt the video rate accordingly, in order to optimize the received video quality. Estimation can be performed by requesting receiver buffer occupancy status (to prevent buffer underflow/overflow) and combining receiver buffer status with bandwidth estimation